Social Cognitive Intervention: Improving Coping Ability of Rural Adolescents with Educational Stress (Medico Legal Update, 2021)
Educational Stress affects the both students’ mental health and physical health. Mounting demand of thesociety, and various academic requirements make some students to perceive education as stressful task.Particularly conditions of the students from the rural area are most vulnerable as they getlack of guidanceand academic related support from their family. Students usually perceive high educational stress when theythink that academic demands are unattainable or above their capacity. Objective of the current study is to findout the efficacy of social cognitive intervention in improving the coping ability of rural adolescent studentswith the educational stress. 100 students were selected as a sample from the rural area of Coimbatore district,Tamil Nadu by using purposive sampling method. Single group pre-test, post-test and follow up researchdesign were used. Statistics used include mean, SD, repeated measure ANOVA and post-hoc were used toanalyze the data. Results showed that rural adolescent students had gained their coping ability in educationalstress after the social cognitive intervention.